Student Organization Advisers’ Planning, Leading and Controlling Skills: Bases for a Strategic Training Design - Del Pilar, Patricia Denise (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the planning, leading, and controlling (PLC) skills of student organization advisers handling the Supreme Pupil Government (SPG) and Supreme Student Government (SSG) in the 4th Congressional District of Iloilo and developed a strategic training design to enhance these competencies. Anchored on Transformational Leadership Theory, Prescriptive Advising Theory, and Integrative Advising Theory, the study employed a quantitative-descriptive research design. Data were collected from 116 advisers through a semi-adopted survey questionnaire consisting of 60 items, validated by experts and tested for reliability. Statistical tools such as frequency count, mean, standard deviation, t-test, Kruskal-Wallis test, and ANOVA were used to analyze the data. Findings revealed that advisers demonstrated high planning skills and very high leading and controlling skills. No significant differences were found in most demographic variables, except for years of advisership influencing planning skills, and selected variables affecting leading and controlling skills. Significant moderate positive relationships were identified among planning, leading, and controlling skills, indicating their interrelated and complementary nature. Despite high overall ratings, gaps were observed in planning-related areas, particularly in resource allocation, strategic planning, and technology integration, which informed the development of a strategic training design. The study concludes that while advisers possess strong managerial competencies, targeted interventions are necessary to strengthen planning-related skills. It recommends the implementation of structured training programs focusing on enhancing planning, leading, and controlling competencies, particularly for less experienced and secondary-level advisers. This study supports SDG 4 – Quality Education, SDG 8 – Decent Work and Economic Growth, and SDG 16 – Peace, Justice, and Strong Institutions by promoting leadership development and participatory governance in schools. It contributes to educational, socio-economic, and institutional sustainability by strengthening adviser capacity, improving student leadership systems, and supporting long-term organizational effectiveness.